The Effect of Free Cash Flow, Leverage, Financial Distress, and Ownership Structure on Earnings Management in Consumer Non-Cyclical Companies (2022-2024) - Rianida, Melycha Putri; Setiawati, Erma (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
Earnings management involves managers adjusting financial reports to achieve specific objectives, which can affect the transparency of information received by stakeholders. Earnings management is conditioned by a constellation of internal firm-level attributes, including free cash flow availability, capital structure intensity, financial vulnerability, and ownership configuration, all of which may recalibrate managerial incentives to intervene in the financial reporting process. Focused on consumer non-cyclicals companies on the IDX, this study tests hypotheses concerning the drivers of earnings management, specifically free cash flow, leverage, financial distress, and ownership structure. The quantitative analysis, using secondary data (2022-2024) and SPSS 27 on a purposively sampled set of 89 observations, confirms the significant roles of free cash flow and leverage. However, it finds no empirical support for the effects of financial distress or managerial ownership. The findings highlight key governance and analytical implications. The significant roles of free cash flow and leverage call for stronger oversight of discretionary cash and debt to limit reporting opportunism. The insignificant effect of managerial ownership suggests weak alignment of manager, shareholder interests, while financial distress does not appear to drive manipulation. For investors and regulators, the results emphasize prioritizing cash flow and leverage analysis when assessing reporting quality.